2020
DOI: 10.5114/hm.2020.89916
|View full text |Cite
|
Sign up to set email alerts
|

Pokémon Go did not increase step count or distance travelled among college students

Abstract: Purpose. Physical inactivity is a well-known problem in the United States, especially among the younger population. Pokémon Go (PG) is a mobile game that has players catch Pokémon while walking in the real world. the purpose of this study was to assess the effect of playing PG on student physical activity. Methods. Overall, 27 healthy undergraduate students participated in a 2-week study. they were randomly assigned to either PG-playing group or control group. Fitbit Charge HR devices were deployed for 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Probably, the most extensively studied Mobile Augmented Reality (MAR) game is Pokémon Go. Schade et al [11] evaluated the influence of playing Pokémon Go on the physical activity of students and found that the amount of distance travelled by university students did not increase. Madrigal-Pana et al [12] examined the perception of videogames and the use of Pokémon Go in Costa Rica and identified positive and negative perceptions of videogames mediated by age and level of education and that attitudes towards videogame playing depended on age and gender.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, the most extensively studied Mobile Augmented Reality (MAR) game is Pokémon Go. Schade et al [11] evaluated the influence of playing Pokémon Go on the physical activity of students and found that the amount of distance travelled by university students did not increase. Madrigal-Pana et al [12] examined the perception of videogames and the use of Pokémon Go in Costa Rica and identified positive and negative perceptions of videogames mediated by age and level of education and that attitudes towards videogame playing depended on age and gender.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, only the parent article was included. Finally, 36 articles [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] were included for this review.…”
Section: Resultsmentioning
confidence: 99%
“…In 14 studies [ 25 , 26 , 29 , 32 , 34 , 36 , 38 , 40 , 43 , 45 , 47 , 50 , 52 , 53 ], PA was assessed solely with subjective measures such as the International Physical Activity Questionnaire. Eight studies [ 21 , 24 , 28 , 30 , 33 , 35 , 39 , 41 ], incorporated only objective measures to assess participants’ PA such as pedometers, accelerometers, wrist or arm-worn activity sensors, heart rate monitors, and mobile applications, such as the iPhone Health app, step-counting app, and ecological momentary assessment app. Finally, five studies [ 23 , 37 , 46 , 48 , 49 ] incorporated both subjective and objective assessments of PA, in which most of the objective measures used health or step-counting mobile applications.…”
Section: Resultsmentioning
confidence: 99%
“…Probably, the most extensively studied Mobile Augmented Reality (MAR) game is Pokémon Go. Schade et al [11] evaluated the influence of playing Pokémon Go on the physical activity of students and found that the amount of steps or distances travelled by university students did not increase. Madrigal-Pana et al [12] examined the perception of videogames and the use of Pokémon Go in Costa Rica and identified positive and negative perceptions of videogames mediated by age and level of education and that attitudes towards videogame playing depended on age and gender.…”
Section: Introductionmentioning
confidence: 99%